2022
DOI: 10.3389/fpls.2022.924162
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transcriptome and metabolome analyses reveal the adaptation of Antarctic moss Pohlia nutans to drought stress

Abstract: Most regions of the Antarctic continent are experiencing increased dryness due to global climate change. Mosses and lichens are the dominant vegetation of the ice-free areas of Antarctica. However, the molecular mechanisms of these Antarctic plants adapting to drought stress are less documented. Here, transcriptome and metabolome analyses were employed to reveal the responses of an Antarctic moss (Pohlia nutans subsp. LIU) to drought stress. We found that drought stress made the gametophytes turn yellow and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 76 publications
1
3
0
Order By: Relevance
“…Studies have shown that CHS is an essential rate-limiting enzyme in the pathway that produces flavonoids and is necessary for regulating plant growth, development, and abiotic stress resistance [ 73 ]. All of these results supported earlier research and indicated that the biosynthesis pathways of phenylpropanoids and flavonoids, especially CHS genes and apigenin, were involved in the response of S. miltiorrhiza to drought stress [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Studies have shown that CHS is an essential rate-limiting enzyme in the pathway that produces flavonoids and is necessary for regulating plant growth, development, and abiotic stress resistance [ 73 ]. All of these results supported earlier research and indicated that the biosynthesis pathways of phenylpropanoids and flavonoids, especially CHS genes and apigenin, were involved in the response of S. miltiorrhiza to drought stress [ 20 ].…”
Section: Discussionsupporting
confidence: 89%
“…Combining transcriptome and metabolomic analyses, researchers have hypothesized that P. nutans strongly relies on the plant hormone signaling pathway and flavonoid metabolism pathway, as well as stress-related genes involved in these pathways, such as NCED3, PP2C, and PYL, which are involved in the ABA signaling pathway. In addition, stress-related genes also included AOS and JAZ in the JA signaling pathway, CHS, FLS, FNS, and UFGT in the flavonoid pathway, and transcription factors ( ERF and DRE B) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that acquisition of environmental stress tolerance in Antarctic mosses by changing fatty acid metabolism requires relatively prolonged exposure to environmental stresses. Although most previous studies using Antarctic mosses have examined changes in gene expression pro les after single arti cial stress treatments for short periods (a few hours to several days) 4,5,6,7 , longer periods of stress treatments may be required to clarify actual mechanisms of environmental stress tolerance in Antarctic mosses.…”
Section: Discussionmentioning
confidence: 99%
“…When plants are exposed to severe environments, stress response genes, such as myelocytomatosis (MYC) genes, myeloblastosis (MYB) genes, ethylene-responsive element binding factor (ERF) genes and dehydration-responsive element binding (DREB) genes, are induced, and subsequently various stress responses including expression of molecular chaperone proteins, production of antioxidants such as avonoids, accumulation of sugars and lipids, and increase in membrane uidity through increase of unsaturated fatty acids occur 1,2,3 . In Pohlia nutans, one of the mosses grown in Antarctica, changes in gene expression pro les have been investigated in response to arti cial stress treatments such as high salinity, low temperature and drought 4,5,6,7 . In these studies, expression of transcription factor genes involved in environmental stress response and tolerance (e.g., MYC, MYB, ERF and DREB genes), genes involved in signaling of plant hormones such as abscisic acid (ABA) and jasmonic acid (JA), and antioxidant biosynthesis genes have been shown to be induced by arti cial stress treatment.…”
Section: Introductionmentioning
confidence: 99%